The Influence of Assistance and the Success of Early Breastfeeding Initiation on Maternity Mothers - Sukaisi Sukaisi; Safrina Safrina (Postgraduate, University of Mataram, 2024)
Colostrum, which is yellowish breast milk, is considered vital because it is the first immunization for newborns and plays a significant role in the newborn's immune defence system. This research aimed to determine the effect of assistance in early breastfeeding initiation and the success of early breastfeeding initiation among mothers giving birth at the Independent Midwife Practice in Pematangsiantar City. The method used in this research was a quasi-experiment with a two-group design pretest-posttest with the control group, which was carried out on 67 mothers divided into two groups, using consecutive sampling (n=34 and unaccompanied mothers n=33). Assistance in the form of providing information on Early Breastfeeding Initiation (EBI) using materials, leaflets, and AVA/videos. The Early Breastfeeding Initiation Satisfaction Questionnaire was adopted from the Maternal Breastfeeding Evaluation Scale. The non-parametric Wilcoxon test was used for testing. Testing used the SPSS.The results of this study showed a significant relationship between mothers' knowledge and satisfaction with success before and after being given the intervention with (p=0.001) and (p=0.025). Assistance for mothers giving birth will increase the success of women in labour to breastfeed their babies as early as possible.